Optimizing Routine and Disaster Prehospital Care Through Improved Emergency Medical Services Oversight. (1st October 2021) - Abir, Mahshid; Forman, Jane; Taymour, Rekar K.; Brent, Christina; Nallamothu, Brahmajee K.; Scott, Jaqueline; Wahl, Kathy
ABSTRACT: Objective: To identify modifiers of emergency medical services (EMS) oversight quality, including facilitators and barriers, and inform best practices and policy related to EMS oversight and system performance. Methods: We used a qualitative design, including 4 focus groups and 10 in-depth, 1-on-1 interviews. Primary data were collected from EMS stakeholders in Michigan from June to July 2016. Qualitative data were analyzed using the rapid assessment technique. Results: Emergent themes included organizational structure, oversight and stakeholder leadership, interorganizational communication and relationships, competition or collaboration among MCA stakeholders, quality improvement practices, resources, and needs specific to rural communities. Conclusions: EMS is a critical component of disaster response. This study revealed salient themes and modifiers, including facilitators and barriers, of EMS oversight quality. These findings were evaluated in the context of current evidence and informed state policy to improve the quality of EMS oversight and prehospital care for both routine and disaster settings. Some were particular to geographic regions and communities, whereas others were generalizable.